MEDIATIZATION OF ISLAMIC DOCTRINE IN A NEW ERA OF DIGITAL INDONESIA: The Case of á¸¤adÄ«th on DajjÄl - Chandra, Agus Firdaus; Putra, D. I. Ansusa (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2019)
This research is a study of the mediatization of the á¸¥adÄ«th on DajjÄl (the anti-Christ) in the context of media culture. Mediatization of the á¸¥adÄ«th through illustrations allows every Muslim to understand the stages and events that will occur at theÂ End of the Time (Ä€khir al-ZamÄn). Such á¸¥adÄ«th is pre-actual doctrinal texts in Islam. This article uses the theory of mediatization that has a close link with the discipline of media studies and religiosity.Â We argue that the á¸¥adÄ«th illusÂtration as an expression of religious beliefs is a continuation of the massive use of technology in understanding religious doctrines. On the other hand, the illustration of the á¸¥adÄ«th. á¸¤adÄ«th on the DajjÄl in digital media has formed a new pattern in the understanding of á¸¥adÄ«th from abstract-imaginative to concrete-imaginative. The illustration of the DajjÄl has become an indication of the widespread role of the media in the spread of Islamic doctrines, and its changing role from being dominated by the texts to being dominated by the logic of religion. This research uses the theory of mediatization with the approach of media culture. The data is obtained from footage of such á¸¥adÄ«th documentary airing on YouTube accounts. These shows usually refer to preachers who are concerned with conveying the contents of the á¸¥adÄ«th.